2015
DOI: 10.1097/hjh.0000000000000616
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between inter-arm blood pressure differences and future cardiovascular events in coronary artery disease

Abstract: IADs were increased in CAD patients and correlated with its severity. Greater than 10  mmHg of IAD was independently associated with future cardiovascular events. Assessing IAD by ABI measurement may facilitate risk stratification in CAD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 41 publications
1
33
6
1
Order By: Relevance
“…The median IASBPD of 4.5 mmHg obtained in the present study was somewhat greater than that reported in other studies . This might be due, at least in part, to the advanced age of the participants in the present study.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…The median IASBPD of 4.5 mmHg obtained in the present study was somewhat greater than that reported in other studies . This might be due, at least in part, to the advanced age of the participants in the present study.…”
Section: Discussioncontrasting
confidence: 83%
“…Differences in blood pressure values between the right and left arms are usually minimal in healthy individuals, but an increase in interarm systolic blood pressure difference (IASBPD) is not uncommon in a clinical setting . Recent studies have highlighted the significant association between IASBPD and risk factors of atherosclerosis . Several studies and a meta‐analysis mostly involving individuals with increased cardiovascular risk reported significant independent associations of IASBPD ≥10 mmHg with increased cardiovascular morbidity and mortality .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This view is supported by some published work (Olmedillas et al, 2010) and it has been suggested that larger circumference arms may be associated with higher measured SBP (Loenneke et al, 2016). Furthermore, because of the widely reported potential significance of inter-arm SBP differences as a predictor of cardiovascular morbidity (Cao et al, 2015;Tokitsu et al, 2015;Zhou et al, 2016;Kranenburg et al, 2017;Hirono et al, 2018) it was believed that the issue concerning the role that handedness might play in such inter-arm pressure differences was of significance and should be specifically addressed. A third motivating factor was that most prior assessments of inter-arm pressure differences focused on either older persons or those with already present cardiovascular symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[8] However, a meta-analysis on the prevalence of IAD has shown a very variable proportion of subjects (1.4-38%) with IAD more than 10 mmHg. [7,[23][24][25][26][27] Various pathological causes have been considered as leading to an increase in interarm BP differences such as atherosclerosis, vasculitis, fibromuscular hyperplasia, connective tissue, and thoracic outlet compression. [10][11][12][13][14][15] In the absence of anatomic obstruction, interarm differences in SBP were thought to be related to some intrinsic property of the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%